Pengaruh Sikap Pada Mata Pelajaran Kimia dan Konsep Diri terhadap Prestasi Belajar Kimia - Novrita Mulya Rosa (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2012)
The purpose of this study was to determine the effect of attitude on the subjects of chemistry and self-concept to chemistry learning achievement. Survey research samples totaled 75 students of class X from Private Senior High Sub-district of Cilandak South Jakarta. The data was collected by administering questionnaires and achievement tests to carry out the study. The results showed by the regression equation Y=-12.983 + 0.300 SK + 0.390 KD. Variable attitude on the subjects of chemistry and self-concept of students together to have a significant influence on learning achievement of students, this is indicated by the coefficient determination R2= 0.777 with Fvalue test =125,400 greater than Ftable=3,12. While testing the regression coefficient on the variable attitude o the subject of chemistry t-test = 6,288 and testing the regression coefficients on the self-concept obtained by calculating the t-test=5,397, both are more than t-table=1,993.